Big Five Traits of Sir Walter Elliot in Jane Austens Persuasion - Putri, Miya Aryatno (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Big five personality traits known as five factor model (FFM) is a set of five broad trait dimensions or domains to describe the ones traits of personality. In this research, the researcher examined big five traits aspects from Sir Walter Elliot on the novel of persuasion Jane Austen, using McCrae theory. The researcher also used documentation techniques and qualitative methods to collect data on the peripheral characters in this movie. The researcher managed to find 8 data: The data found were Conscientiousness (1), Extroversion (3), Agreeableness (2), Shallow Neuroticism (1), Openness to Experience (1) in Sir Walter Elliot big five traits. Extroversion gives big impact to his personalities compared the other aspects